Evaluasi Penerapan Sistem Pengendalian Risiko Di Lingkungan Perguruan Tinggi Negeri - Yeza Putri Zahri; Irsyad, Irsyad; Tia Ayu Ningrum (CV. ITTC INDONESIA, 2025)
This study aims to evaluate the implementation of risk control systems in State Universities (PTN) based on the risk control principles applicable in public sector governance. The evaluation was conducted to determine the extent to which PTNs implement risk identification, analysis, mitigation, and monitoring processes in their operational activities. This study used qualitative methods through document studies, observations, and interviews. The results indicate that the implementation of risk control in PTNs has been running moderately but is not yet fully documented and integrated. Several aspects that require improvement include risk documentation, monitoring of mitigation implementation, and integration of risk information systems.